Developing an Integrated Set of Production Planning and Control Models - WANG, HUI (2012)
This paper proposes an integrated set of production planning and control models that can be applied in the Push system (Make-to-stock). The integrated model include forecasting, aggregate planning, materials requirements planning, inventory control, capacity planning and scheduling. This integrated model solves the planning issues via three levels, which include strategic level, tactical level and operational level. The model obtains the optimal production plan for each product type in each period, so that it can acquire high quality products at lower cost, lower inventory, and a high level of performance. This proposed integrated model is tested based on a shoe manufacturing company which has two main types of shoes with stationary demand and seasonal demand pattern respectively. The results of the production plans demonstrate that the proposed model generates good and feasible solutions to specific production problems.